Low pressure biomethane gas adsorption by activated carbon - Sirichai Koonaphapdeelert (2018)
© 2017 International Energy Initiative The objective of this research is to study the adsorption of biomethane gas by several different absorbents. The ultimate goal was to create a cost effective and safe fuel tank for use in domestic cooking applications in rural Thailand. Biomethane is a cleaned and upgraded fuel derived from biogas. It contains a minimum of 80% methane (v/v) with the remainder composed mostly of carbon dioxide. Specifically, the effects of pressure and temperature on the biomethane adsorption capacity of five different absorbents in a 28 l tank were studied. The pressure ranged between 3 and 9 MPa while the temperature range was 15–25 °C. The results showed that the adsorbent, Activated Carbon 3, had the highest biomethane adsorption capability. At higher pressures, greater biomethane adsorption was observed with the highest adsorption value of 164.3 ± 0.5 g/l obtained at 9 MPa. Temperature had a smaller effect with higher temperatures producing less adsorption. At 9 MPa, as the temperature increased from 15 to 25 °C, the adsorbed biomethane decreased by 8%. The degradation in performance of the adsorbent was investigated and found to be negligible over 500 filling/emptying cycles. The selective adsorption of methane over the other biomethane constituents was investigated and also found to be negligible over 500 cycles. The Langmuir adsorption model was applied to estimate the maximum absorption capacity of each absorbent.